A Study On Influence Of Internet On Social And Academic Life Of Student (Journal of Namibian Studies : History Politics Culture, 2022)
Today, the internet is largely acknowledged as a potent tool of education in addition to a method of communication. Internet use has both positive and negative effects on students' academic performance. Although it has a mixed impact on politics and morality, the internet is generally good for education. The goal of the current  study is to find the overall influence of internet usage on the undergraduate and postgraduate students of cotton university. A descriptive research method is used for the study and the data were collected using a random sampling technique. A total of 38 students were selected randomly for the study from the population. According to the study’s findings The majority of Cotton University students use the internet every day to obtain course materials, to get ready for exams, and to stay up to date on the newest news. Internet has an impact on Cotton University students' social lives as well. They also made use of the internet to relax after a stressful day and update their knowledge on how society was developing. Additionally, it was observed that social networking site addiction is a challenging issue faced by Cotton University students, and that there is a negative impact of the internet on students' academic and social lives as they frequently become distracted from their goals.